UJI EFEKTIVITAS EKSTRAK ETANOL 70% DAUN SUKUN (Artocarpus altilis) TERHADAP PENYEMBUHAN LUKA SAYAT PADA KELINCI PUTIH JANTAN NEW ZEALAND WHITE - Syahadatun, Iknacia; Hidayat, Rahmat; Septiarini, Anita Dwi (Universitas Imelda Medan, 2025)
Cuts are a common type of wound and require proper treatment to accelerate the healing process and prevent infection. Breadfruit leaves (Artocarpus altilis) are known to contain flavonoids, tannins, and saponins, which have anti-inflammatory and antiseptic properties and can stimulate tissue regeneration. This study aimed to determine the effectiveness of a 70% ethanol extract of breadfruit leaves on wound healing and to determine the most effective concentration. This study used an experimental method with male New Zealand White rabbits as test animals. The rabbits were divided into six treatment groups: a positive control (bioplacenton®), a negative control (distilled water), no treatment, and groups with extract concentrations of 25%, 50%, and 75%. The treatments were administered twice daily for 14 days. Data were analyzed using a one-way ANOVA followed by a LSD (Least Significant Different. The results showed that a 70% ethanol extract of breadfruit leaves at a concentration of 75% provided the best wound healing effect, nearly comparable to the positive control. This effectiveness is thought to stem from active compounds that work synergistically to accelerate tissue regeneration.